Environmental Criteria for sustainable urban site selection (Journal of Planner and Development, 2016)
This paper focuses on the environmental standards that should be taken into account when selecting the urban site. These standards subject any area to the decisions based on criteria respect the ecological nature and urban characteristics reaching urban sustainability which should decide the suitability of various sites for various uses. This will achieved by studying the site characteristics and its environmental resources briefly (using Baghdad city characteristics ), which can be developed into a standard matrix with weights to each criterion in terms of its importance, also it could be collected to give the best results for knowing the site suitability for his urban environmental performances.